A Study on Entangled Photon Pairs in Graded-Index Optical Fibers - Dinleyici, Mehmet Salih; Ekici, Çağın; Ekici, Çağın (Izmir Institute of Technology, 2021)
Quantum optics offer new possibilities, new approaches, and potentially groundbreaking new technologies whose backbone is based on creation, manipulation, and detection of special quantum states of light. The main objective of the thesis is to present a study of spontaneously arisen heralded entangled photon-pairs which play crucial role in emerging quantum enhanced technologies. We have mainly investigated discrete transverse-spatial-mode entangled photon-pairs in waveguide, because it intrinsically offers infinite dimension. Entangled states of higher dimensional systems enable realization of quantum information schemes that can offer higher information density coding and show more error resilience than can be achieved with lower dimensional systems. In this context, we have exploited a graded-index optical fiber as photon-pair-generation platform via nonlinear intermodal-four-wave mixing (FWM), since the fiber may allow different FWM processes to overlap in spectral domain, resulting in an entangled pair of spatial qubits. We have also probed joint spectral properties of the generated photons to show capability of hyperentanglement in frequency and transverse mode. We have discussed spatial Wigner function and its realization to characterize spatial properties of the quantum state. We have shown that entanglement can be verified through a violation of the Clauser - Horne - Shimony - Holt (CHSH) inequality based on spatial Wigner function and coupled-mode theory. This thesis also includes basic analysis of transverse-mode entangled photon-pair distribution in a lossy-dispersive medium. Finally, the ways to follow and the quantities to measure are touched upon. Thus, we have explained the generation and four different detection schemes, relying on a combination of photon-number statistics, joint spectral properties, and spatial entanglement measurements.

Kuantum optiği, yeni olanaklar, yeni yaklaşımlar ve temeli özel kuantum ışık durumlarının yaratılmasına, manipülasyonuna ve tespitine dayanan potansiyel olarak çığır açabilecek yeni teknolojiler sunuyor. Tezin temel amacı, kuantum hesaplama ve kuantum iletişimi gibi gelişmekte olan kuantum teknolojilerinde de önemli bir rol oynayan, kendiliğinden ışınan dolanık haberci foton çiftlerinin incelenmesidir. Ağırlıklı olarak dalga kılavuzundaki ayrık enine uzamsal mod dolanık foton çiftlerini araştırdık, çünkü bu durum doğası gereği sonsuz boyut sunuyor. Yüksek boyutlu sistemlerin dolanık durumları, daha düşük boyutlu sistemlerle elde edilebilecek olandan daha yüksek bilgi yoğunluğu kodlaması sunabilen ve hatalara daha dirençli kuantum bilgi şemalarının gerçekleştirilmesini sağlar. Bu kapsamda, derece indisli bir optik fiberi, doğrusal olmayan modlar arası dört-dalga karışımı yöntemiyle bir foton çifti oluşturma platformu olarak kullandık, çünkü bu fiber farklı dört-dalga girişim işlemlerinin spektral alanda örtüşmesini sağlayıp dolanık uzamsal kübit çiftinin ortaya çıkmasını sağlayabilir. Ayrıca, frekans ve enine modda hiper dolanma kabiliyetini göstermek için üretilen fotonların ortak spektral özelliklerini de inceledik. Kuantum durumunun uzamsal özelliklerini karakterize etmek için uzamsal Wigner fonksiyonunu ve bunun gerçeklenmesini tartıştık. Dolanıklığın uzamsal Wigner fonksiyonuna ve kuple-mod teorisine dayanan CHSH eşitsizliğinin ihlali yoluyla doğrulanabilineceğini gösterdik. Bu tez aynı zamanda kayıplı ve ayırıcı (dispersiyonlu) bir ortamda temel bir enine mod dolanık foton dağıtım analizini de içerir. Son olarak, izlenecek yollara ve ölçülecek niceliklere değinilmiştir. Bu bağlamda, foton sayısı istatistikleri, ortak spektral özellikler ve uzaysal dolanıklık ölçümlerinin bir kombinasyonuna dayanarak, üretim ve dört farklı algılama şemasını kısaca açıkladık.
Derece İndisli Optik Fiberlerde Dolanık Foton Çiftleri Üzerine Bir Çalışma
Thesis (Doctoral)--Izmir Institute of Technology, Electronics and Communication Engineering, Izmir, 2021
Includes bibliographical references (leaves. 118-131)
Keywords: Quantum optics; Fiber optics; Nonlinear optics